Debating graduation - Michael MacLennan; Fábio Veras Soares; Ian Orton (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
Since its inception in Bangladesh in 2002, the Graduation Approach has received much attention, including in mainstream media outlets. Beyond this positive media acclaim, momentum has gathered behind graduation as an important social policy instrument. There has been a proliferation in the implementation of new graduation-inspired programmes.
Keywords: 330; social protection; debating; graduation